2013
DOI: 10.21837/pmjournal.v11.i2.119
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Pedestrian Index Into Googlemaps

Abstract: The trend for new urbanism which encourages public transportation usage has increasingly focused on pedestrian facilities. Pedestrian fac ilities can be defined as facilities that continuously provide pedestrians with safe access to land uses. Unfortunately, roadway design prioritizes the needs of motorists while putting pedestrians at ri sk. A number of studies have developed methods to determine pedestrian Level of Service (LOS). However, none have considered the road hierarchy which has a different design s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to the basic subdivision into four families of factors, the selected walkability evaluation methods revealed that even though, overall, many studies of walkability transversally touch all the families, thus proving to adopt a multidimensional approach, single methods differ in the emphasis given to certain families and in the way of operationalizing the measurement. Some studies focus mainly on the safety and efficiency of space [81,85], others look at the attractiveness of the city [1,28] and still others are more sensitive to pleasantness [7,10,86,87].…”
mentioning
confidence: 99%
“…According to the basic subdivision into four families of factors, the selected walkability evaluation methods revealed that even though, overall, many studies of walkability transversally touch all the families, thus proving to adopt a multidimensional approach, single methods differ in the emphasis given to certain families and in the way of operationalizing the measurement. Some studies focus mainly on the safety and efficiency of space [81,85], others look at the attractiveness of the city [1,28] and still others are more sensitive to pleasantness [7,10,86,87].…”
mentioning
confidence: 99%